2022
DOI: 10.1101/2022.04.17.22273906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolving SARS-CoV-2 epidemic in Africa: Insights from rapidly expanding genomic surveillance

Abstract: Investment in Africa over the past year with regards to SARS-CoV-2 genotyping has led to a massive increase in the number of sequences, exceeding 100,000 genomes generated to track the pandemic on the continent. Our results show an increase in the number of African countries able to sequence within their own borders, coupled with a decrease in sequencing turnaround time. Findings from this genomic surveillance underscores the heterogeneous nature of the pandemic but we observe repeated dissemination of SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Expanding genomic sequencing capabilities, especially in LMICs, is a global priority 26 and current investments in sequencing must continue. 27,28 Simultaneously, sustained investments in public health systems are required to expand access to, and availability of, diagnostic testing to underpin SARS-CoV-2 surveillance programs. Here, we primarily focused on LMICs but our findings on the impact of testing rates and representativeness on genomic surveillance programs are equally important for HICs as they consider dismantling parts of their testing and surveillance infrastructure in the post-crisis phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding genomic sequencing capabilities, especially in LMICs, is a global priority 26 and current investments in sequencing must continue. 27,28 Simultaneously, sustained investments in public health systems are required to expand access to, and availability of, diagnostic testing to underpin SARS-CoV-2 surveillance programs. Here, we primarily focused on LMICs but our findings on the impact of testing rates and representativeness on genomic surveillance programs are equally important for HICs as they consider dismantling parts of their testing and surveillance infrastructure in the post-crisis phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the Eta variant (B.1.525) emerged in Nigeria in late July, with high levels of export to Europe reflected in the genomic and estimated export index. The true extent of bidirectional transmission with other African nations will be severely underestimated in phylogeographic reconstructions, as Africa remains disproportionately undersampled despite heroic efforts 28 . Our findings should be interpreted in the light of our own sampling fraction, which was 0.026%.…”
Section: Discussionmentioning
confidence: 99%
“…In the space of 2 years and under the extremely heavy constraints of the pandemic, the Africa CDC PGI 38 has expanded next‐generation sequencing capacity in Africa from just 7 countries in November 2019 to 31 countries in January 2022. 39 …”
Section: Leveraging Hiv Vaccine Research In South ...mentioning
confidence: 99%
“…The newly formed Network for Genomic Surveillance in South Africa (NGS-SA) 37 In the space of 2 years and under the extremely heavy constraints of the pandemic, the Africa CDC PGI 38 has expanded next-generation sequencing capacity in Africa from just 7 countries in November 2019 to 31 countries in January 2022. 39 South African laboratories have also been heavily involved in…”
Section: Le Ver Ag Ing Hiv Vaccine Re S E Arch In South Afric a To Co...mentioning
confidence: 99%
See 1 more Smart Citation